Septic Abortions: An Outcome of Criminal Abortion - Urooj Husain, Imran Jawaad, Saima Manzoor, Durdana Zafar, Zubia Iqbal, Nazia Yasmin, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Abortion is considered illegal in many countries, same is true in Pakistan. In spite of all considerations no law currently support abortion, it is moral value of the doctor to justify this act. The ratio of cases resulting in abortion with the consent of mother are usually not reported at the government hospital that is why the actual figure remain unclear. Majority of cases of illegal abortion are observed among females out of wedlock, who do not want to disclose it to their family and friends, so they seek a secret way to get rid of this burden. The ways adopted for abortion are not legal and quite unhygienic which places the female at risk of sepsis or even death. Materials and Methods: A total of 15 cases of septic abortion were reported to Lady Aitcheson Hospital, Lahore during a period of 4 years from 2015 to 2019. All these cases of septic abortion were cases of criminal abortion. Results: Out of 750 cases of abortion only those illegal abortions which got septic were considered in this study. Depending on the symptoms they were divided into three groups. Majority of the cases were between 20-25 years of age and belonged to low socioeconomic group. Out of 15 cases 06 died due to advanced sepsis, 03 recovered with multiple antibiotic for more than two weeks, 02 patients had blood transfusion and recovered, 08 had laparotomy and 02 had laparotomy with hysterectomy. Conclusion: The present study concludes that criminal abortion although illegal and is prevailing globally cannot by prevented. However, legal reforms need to be made so that whenever such cases are encountered proper medical cover and early referral to a hospital can prevent mortality among such females